Ritmo de queda dos carrapatos Amblyomma cajennense, Amblyomma parvum, e Rhipicephalus sanguineus de hospedeiros experimentais - Silva, Tathiane de Lima (2013)
Tick is the main vector of infectious diseases to animals and is an important vector to humans as well. Tick drop-off rhythm from hosts defines host distribution in the environment and thus is part of the epidemiology of tick-borne diseases. Drop-off rhythm of neotropical ticks is overall unknown. We herein investigated the drop-off rhythm of a few tick species found in Brazil and that are already (Amblyomma cajennense, Rhipicephalus sanguineus) or potentially (Amblyomma parvum) important infectious agent vectors. Tick drop-off rhythm was evaluated during infestation of hosts within feeding chambers. Search behavior of Rhipicephalus sanguineus ticks for hosts was also evaluated. R. sanguineus larvae and nymphs dropped off from rabbits overwhelmingly during photophase (86 and 70%, respectively). Adults from the same tick species dropped off similarly in photo (48%) and scotophase (52%). Larvae and nymphs of A.parvum ticks dropped off in photophase (62 and 66%, respectively). Argentinian and Brazilian populations of adult A.parvum ticks detached from rabbits in scotophase (68 an 71%, respectively). A. cajennense nymphs detached from rabbits in both photophase (43%) and scotophase (57%). On the other hand, nymphs and adults from the same tick species detached from pigs in photophase (76 and 78%, respectively). It was observed that adult R. sanguineus ticks searched for rabbits as soon as the host was available irrespective if this occurred in the morning or afternoon or continuously or discontinuous. Results showed that each tick species and instar have preferential drop-off timing. Further investigation is needed to determine factors that drive such drop-off rhythm of each tick species.